Lắng đọng hóa học cacbon từ pha hơi (CVD) vào vật liệu graphit lỗ xốp tạo pyrographit tỷ trọng cao - Hùng, Nguyễn Đức; Đường, Đặng Văn; Hoàn, Nguyễn Vĩ; Thoa, Lê Thị (Vietnam Journal of Chemistry, 2014)
Chemical vapour depostion technology has been used for the system including: spongy graphite, propane-butane and argon at the temperature of 800oC. After the CVD the condensed material: nanopyrographite was well synthetized.